Respuesta :
Answer: [tex]x=-\frac{4}{3}[/tex]
Step-by-step explanation:
[tex]2(x)+2(2)=2(\frac{x}{2})-2(x)[/tex]
Remove all those parentheses by multiplying. Note: 2 and 2 cancel out.
[tex]2x+4=x-2x[/tex]
Subtract 2x
[tex]4=x-2x-2x[/tex]
Combine like terms;
[tex]4=-3x[/tex]
Divide by -3
[tex]\frac{4}{-3}=x[/tex]
Rewriting it;
[tex]x=-\frac{4}{3}[/tex]
Answer:-4/3
Step-by-step explanation:
2(x)+2(2)=2(x/2)-2(x)
Remove brackets by multiplying through
2x + 4=x - 2x
Collect like terms
2x+2x-x=-4
3x=-4
Divide both sides by 3
3x/3=-4/3
x=-4/3